2021
DOI: 10.1186/s13046-021-01919-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of the circadian clock in cancer hallmark acquisition and immune-based cancer therapeutics

Abstract: The circadian system temporally regulates physiology to maintain homeostasis. Co-opting and disrupting circadian signals appear to be distinct attributes that are functionally important for the development of a tumor and can enable or give rise to the hallmarks that tumors use to facilitate their initiation, growth and progression. Because circadian signals are also strong regulators of immune cell proliferation, trafficking and exhaustion states, they play a role in how tumors respond to immune-based cancer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 111 publications
0
21
0
Order By: Relevance
“…Nivolumab mainly enhances the activity of T cells against tumor cells. It has long been known that both the functional activity and trafficking of immune cells are regulated over the 24 h by molecular circadian clocks expressed by these cells [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. This is notably the case for T(CD8) lymphocytes, which represent the main target cells of nivolumab [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nivolumab mainly enhances the activity of T cells against tumor cells. It has long been known that both the functional activity and trafficking of immune cells are regulated over the 24 h by molecular circadian clocks expressed by these cells [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. This is notably the case for T(CD8) lymphocytes, which represent the main target cells of nivolumab [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, there has been a paradigm shift on the role of the immune system in cancer therapy, with several new therapies that are now FDAapproved to enhance and even engineer the immune system to attack tumors. Some of these new therapies may benefit from chronotherapy because the tumor molecular clock influences the tumor microenvironment and immune cell infiltration (Cash et al, 2021;Z. Zhang et al, 2021b).…”
Section: Circadian Regulation Of the Tumor Cell Cycle Can Affectmentioning
confidence: 99%
“…Supporting a beneficial effect of tumor clock-dependent immune responses, multiple ROR agonists (e.g. LYC-55716), which are activators of BMAL1 transcription, are now in preclinical and clinical trials, showing good tolerability, safety, and pharmacokinetics in single or combined treatment with existing immune-therapeutic agents (Cash et al, 2021). On the other hand, a recent study with patient-derived glioblastoma stem cells (GSC) revealed that CLOCK and its heterodimeric partner, BMAL1, enhance GSC self-renewal via transcriptional upregulation of olfactomedin-like protein 3 (OLFML3), a proangiogenic chemokine that recruits immune-suppressive microglia into the tumor microenvironment (Chen et al, 2020).…”
Section: Circadian Regulation Of the Tumor Cell Cycle Can Affectmentioning
confidence: 99%
“…Interestingly, a recent animal study showed that enhancing the circadian clock with Dex treatment reduced tumor proliferation and growth in mouse melanoma 73 . Despite their tumor suppressor function, recent clinical reports suggest that GCs may also be implicated in poorer responses to cancer therapies with immune checkpoint inhibitors, such as anti-PD-(L)1, due to their immunosuppressive functions 74 . Given the diurnal fluctuation in endogenous GC levels, it would therefore be important to consider the dose and administration timing of corticosteroids to improve efficacy and safety in their use with immune-based cancer therapies.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, synthetic RORγ agonists have also been reported to enhance antitumor immunity by increasing cytotoxic lymphocyte functions and attenuating immunosuppressive mechanisms 91 . Indeed, the ROR agonist LYC-55716 has been actively implemented in preclinical and clinical trials, showing good tolerability, safety, and pharmacokinetics in single or combined treatment with existing immunotherapeutic agents 74 . Notably, nobiletin, a dietary flavonoid found in citrus fruits, has been recently characterized as an agonist of RORα and RORγ that can induce apoptosis and cell cycle arrest, suppress migration and invasion, inhibit many oncogenic drivers, upregulate tumor suppressors, and increase chemotherapy sensitivity across several cancer cell types 92 .…”
Section: Introductionmentioning
confidence: 99%